Pengembangan Bahan Ajar Digital Berbasis Hots Dengan Memanfaatkan Aplikasi Canva pada Mata Pelajaran IPA Kelas V SD - Putra, Aldo Pramana; Riyoko, Endie; Fakhrudin, Ali (Indonesian Research Journal on Education, 2023)
This research aims to produce a product of digital teaching materials based on HOTS in the subject of Heat and Transfer Science for class V SD Negeri 20 Pemulutan which has valid, feasible, and effective results. This study uses the Research and Development research method (research and development) using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The subjects in this study were 3 validators which included media experts, material experts, and linguists, as well as fifth-grade elementary school students in the one-to-one trial of as many as 3 students, the small group of as many as 9 students, and the pretest-posttest as many as 10 students. The results showed that thevalidity assessment was 81.2% based on validation questionnaire sheets from media experts, linguists, and material experts with the "Very Valid" category, based on student responses questionnaire sheets in small group trials obtained a practicality assessment of 84.7%, and based on the results of the pretest and posttest obtained an N-Gain score of 0.44 with the category "Medium Improvement" according to the N-Gain scale.